Prevalence of frailty syndrome and its associated factors among community-dwelling elderly in East Coast of Peninsular Malaysia - Mohd Hamidin, Fairus Asma; Adznam, Siti Nur’Asyura; Ibrahim, Zuriati; Chan, Yoke Mun; Abdul Aziz, Nur Hafizah (SAGE Publications, 2018)
Objective: Frailty is a clinical syndrome with increased risk of poor health outcomes and particularly prevalent in older adults and community population. The study's aim was therefore to determine the prevalence of frailty and its association with sociodemographic and socioeconomic characteristics, health-related status, and anthropometric measurements among community-dwelling older adults. Methods: A total of 279 older adults aged 60 years and above were randomly selected. Respondents were classified as non-frail (<2 criteria) or frail (≥3 criteria) based on the 'phenotype of frailty'. A binary logistic regression was used to determine predictors of frailty. Results: The prevalence of frailty was 18.3%. The frail older adults were positively associated with advanced age, being unmarried, hospitalisation in the previous year, poor self-rated health, and lower body mass index. Discussion: These results give an overview on underlying effects and guiding actions for prevention programmes functioning to reverse and minimise the adverse effects of frailty syndrome.